2010
DOI: 10.1021/mp100125b
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Biorelevant Dissolution Method Using USP Apparatus 4 in Early Phase Formulation Development

Abstract: Dissolution testing is frequently used to determine the rate and extent at which a drug is released from a dosage form, and it plays many important roles throughout drug product development. However, the traditional dissolution approach often emphasizes its application in quality control testing and usually strives to obtain 100% drug release. As a result, dissolution methods are not necessarily biorelevant and meaningful application of traditional dissolution methods in the early phases of drug product develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
(59 reference statements)
0
10
0
1
Order By: Relevance
“…Okumo et al (89) showed that a dynamic pH change of the dissolution media generated a release profile for montelukast sodium tablets which was able to predict the observed pharmacokinetics when used as input function into GastroPlus software. Fang et al (113) fine-tuned the dynamic dissolution protocol and applied it to food effect studies and as a screening tool in early drug development.…”
Section: Biorelevant Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Okumo et al (89) showed that a dynamic pH change of the dissolution media generated a release profile for montelukast sodium tablets which was able to predict the observed pharmacokinetics when used as input function into GastroPlus software. Fang et al (113) fine-tuned the dynamic dissolution protocol and applied it to food effect studies and as a screening tool in early drug development.…”
Section: Biorelevant Mediamentioning
confidence: 99%
“…However, different FDA guidance documents use different pH ranges to determine the solubility of drug substances: e.g., the biowaiver guideline from 2000 determines the solubility of the highest dose strength in 250 mL or less of aqueous media, over the pH range of 1-7.5 at 37 ± 1°C (124), while the CEDER guide from 1997 uses pH 1.0-8.0 (69), an FDA's draft guidance from 2015 on BDissolution Testing and Specification Criteria for Immediate-Release Solid Oral Dosage Forms Containing Biopharmaceutics Classification System Class 1 and 3 Drugs^uses pH 1 to 6.8 (113).…”
Section: Regulatory View Of Biopharmaceutics Drug Classification Systmentioning
confidence: 99%
“…[1][2][3] These media contain naturally occurring solubilizing agents such as lecithin, bile salts and lipolysis products, which often lead to a higher solubility and faster dissolution of poorly soluble APIs than would be the case in a simple aqueous buffer at the same pH. Dissolution results using biorelevant media have already been proven useful for qualitatively, and in some cases quantitatively, predicting in-vivo drug performance (for example see Galia et al [4] , Sunesen et al [5] , Jantratid et al [6] and Fang et al [7] ). However, quantitative prediction of in-vivo performance directly from dissolution test results can be challenging since various physiological parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…56 However, only few dissolution studies using the USP Apparatus 57 4 have been conducted on extended-release oral dosage forms 58 containing poorly water-soluble drugs (Fotaki et al, 2009;59 Jantratid et al, 2009). In those studies, the discrimination ability 60 was not considered, as the emphasis was put to the prediction of (Fotaki et al, 2009;Fang et al, 2010). 68 Here, as a case example, an appropriate in vitro dissolution test 69 using the USP Apparatus 4 for an extended drug release matrix 70 containing a poorly water-soluble drug was designed based on the 71 release mechanism.…”
mentioning
confidence: 99%